2016
DOI: 10.21273/hortsci.51.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Improving Rooting and Shoot Tip Survival of Micropropagated Transgenic American Chestnut Shoots

Abstract: Many hardwood tree species are being threatened by exotic pests, and for some, only genetic engineering can offer a solution before functional extinction occurs. An example of how genetic engineering can be a useful tool for forest restoration is the transgenic american chestnuts, which contain a wheat oxalate oxidase gene conferring resistance to the chestnut blight. Many hundreds of these trees are needed for field trials and eventual restoration plantings throughout its natural range, but production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…It is believed that such reduction will ease the exit of primordia from the stems as well as help in the growth of new roots, because full-strength media might inhibit rooting, though the response is a species-dependent and probably a genotype-dependent issue. Indeed, rooting rates of microshoots of C. sativa and C. dentata in the presence of full-strength media were satisfactory [ 98 , 112 ]. In addition, better rooting rates and mean number of roots were achieved in C. henryi microcuttings rooted in full-strength media than in half-strength media [ 100 ].…”
Section: Main Factors Influencing the Rooting Responsementioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that such reduction will ease the exit of primordia from the stems as well as help in the growth of new roots, because full-strength media might inhibit rooting, though the response is a species-dependent and probably a genotype-dependent issue. Indeed, rooting rates of microshoots of C. sativa and C. dentata in the presence of full-strength media were satisfactory [ 98 , 112 ]. In addition, better rooting rates and mean number of roots were achieved in C. henryi microcuttings rooted in full-strength media than in half-strength media [ 100 ].…”
Section: Main Factors Influencing the Rooting Responsementioning
confidence: 99%
“…Low concentrations of AC, ranging from 0.2 to 1%, have been successfully used in the rooting of chestnut microshoots [ 33 , 97 ]. Depending on the genotype, the rooting frequencies were increased up to more than two fold in the presence of AC [ 93 , 98 ]. Nonetheless, as IBA was the hormone frequently used and it is believed to be more stable than IAA in culture media and under light conditions [ 131 ], the mode of action of AC in AR remains to be defined.…”
Section: Main Factors Influencing the Rooting Responsementioning
confidence: 99%
“…With the appropriate cytokinin and auxin concentration, chinquapin shoots were strong enough for rooting and surviving after potting ex vitro. As the study on the American chestnut showed that in vitro shoots are recommended only if they have more than six leaves before rooting and are greater than 3 cm in height so they would be large enough to survive after potting (Oakes et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Micropropagation of Castanea species has been investigated on the American chestnut (C. dentata) (Oakes et al, 2013(Oakes et al, , 2016Xing et al, 1997Xing et al, , 1999, the Chinese chestnut (C. mollissima) (Lu et al, 2017;Qi-guang et al, 1986), the European chestnut (C. sativa) (Corredoira et al, 2003;Rodriguez, 1982;Sezgin and Dumano glu, 2014), the Japanese chestnut (C. crenata) (Tetsumura and Yamashita, 2004), and their hybrid chestnut (Cuenca et al, 2017;Vidal et al, 2015). Micropropagation of Castanea species in most of the reports was successful.…”
mentioning
confidence: 99%
See 1 more Smart Citation